2010
DOI: 10.1158/0008-5472.can-09-3492
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Suppresses MLK3-Mediated Apoptosis Sensitivity in ER+ Breast Cancer Cells

Abstract: Little knowledge exists about the mechanisms by which estrogen can impede chemotherapy-induced cell death of breast cancer cells. 17β-Estradiol (E 2 ) hinders cytotoxic drug-induced cell death in estrogen receptor-positive (ER + ) breast cancer cells. We noted that the activity of the proapoptotic mixed lineage kinase 3 (MLK3) kinase was relatively higher in estrogen receptor-negative (ER − ) breast tumors, suggesting that E 2 might inhibit MLK3 activity. The kinase activities of MLK3 and its downstream target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…To delineate the signaling molecules that can regulate ␤-catenin function, we focused on the MAP3K member MLK3, which is known to regulate various cellular pathways (18,19). Subconfluent populations of human cell lines derived from embryonic kidney (HEK-293) and cervical carcinoma (HeLa) were transfected separately with either HA epitope-tagged ␤-catenin alone or in combination with M2-tagged MLK3 wildtype (WT) or K/A forms.…”
Section: Mlk3 Regulates ␤-Catenin Expression In Various Cell Types-mentioning
confidence: 99%
See 1 more Smart Citation
“…To delineate the signaling molecules that can regulate ␤-catenin function, we focused on the MAP3K member MLK3, which is known to regulate various cellular pathways (18,19). Subconfluent populations of human cell lines derived from embryonic kidney (HEK-293) and cervical carcinoma (HeLa) were transfected separately with either HA epitope-tagged ␤-catenin alone or in combination with M2-tagged MLK3 wildtype (WT) or K/A forms.…”
Section: Mlk3 Regulates ␤-Catenin Expression In Various Cell Types-mentioning
confidence: 99%
“…A prominent role of MLK3 in regulating neuronal cell apoptosis is now well established and is believed to involve downstream JNK signaling (17). In addition, recent studies have demonstrated the expression of MLK3 in cancer cells and established its involvement in mediating various prooncogenic pathways (18,19). Cross-talk of Wnt/␤-catenin signaling pathway with another closely linked mammalian MAP3K member TGF␤-activated kinase1 (TAK1) has been reported recently where TAK1 negatively regulates Wnt/␤-catenin pathway (20).…”
mentioning
confidence: 99%
“…The role of MLK family members in cancer has just started to emerge. We have shown regulation of MLK3 activity and downstream signaling in breast cancer cells by estrogen (13) and involvement of MLK3 in gastric cancer cell migration (14). Despite an established role for MLK3 (15) and Pin1 (16) in cell-cycle progression, a detailed mechanism is yet to be explored.…”
mentioning
confidence: 98%
“…Our recent studies with estrogen receptor-positive (ER + ) breast cancer cells showed that the proapoptotic function of MLK3 was blocked by estrogen. 48 We showed that the kinase activity of MLK3 was downregulated by estrogen via activation of the PI3K-AKT pathway. 48 In this report, we also showed that cytotoxic drug, Taxol-induced (Taxol Source, Ivax Laboratories, Florida) cell death requires MLK3 kinase activity and that estrogen antagonizes Taxol-induced cell death via MLK3/MLKs inhibition.…”
Section: Functions Of Mlk Members and Cancer Connectionmentioning
confidence: 94%
“…48 We showed that the kinase activity of MLK3 was downregulated by estrogen via activation of the PI3K-AKT pathway. 48 In this report, we also showed that cytotoxic drug, Taxol-induced (Taxol Source, Ivax Laboratories, Florida) cell death requires MLK3 kinase activity and that estrogen antagonizes Taxol-induced cell death via MLK3/MLKs inhibition. This important study sheds light on the therapeutic potential of MLK3 activators in ER + breast cancer treatment.…”
Section: Functions Of Mlk Members and Cancer Connectionmentioning
confidence: 94%